2020
DOI: 10.34117/bjdv6n3-284
|View full text |Cite
|
Sign up to set email alerts
|

Estoque de volume e biomassa na madeira de Cordia goeldiana Huber (freijó) em sistema agroflorestal multiestratificado

Abstract: Estoque de volume e biomassa na madeira de Cordia goeldiana Huber (freijó) em sistema agroflorestal multiestratificado Volume and biomass stock in Cordia goeldiana Huber (freijó) wood in a multistratified agroforestry system

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…In a study with Tectona grandis wood from an agrosilvi-pastoral system, it was found that when compared with literature results referring to homogeneous plantations, teak wood from an agrosilvi-pastoral system maintained its technological qualities in terms of basic density, the which is a favorable option for the use of this species in the format of associated plantations (Oliveira et al 2020). Also, the biomass values found in Cordia goeldiana wood were consistent with the expected characteristics for species used in an agroforestry system (Mascarenhas et al 2020).…”
Section: Wood Propertiessupporting
confidence: 80%
“…In a study with Tectona grandis wood from an agrosilvi-pastoral system, it was found that when compared with literature results referring to homogeneous plantations, teak wood from an agrosilvi-pastoral system maintained its technological qualities in terms of basic density, the which is a favorable option for the use of this species in the format of associated plantations (Oliveira et al 2020). Also, the biomass values found in Cordia goeldiana wood were consistent with the expected characteristics for species used in an agroforestry system (Mascarenhas et al 2020).…”
Section: Wood Propertiessupporting
confidence: 80%